Antifungal Potential of Pineapple Rind and Foliage Crown (Ananas comosus L. Merr) Waste Extracts Against Dermatophyte and Non-Dermatophyte Fungi - Anindita Riesti Retno Arimurti; Baterun Kunsah; Dita Artanti; Fitrotin Azizah; Yety Eka Sispita Sari (Jurnal FARMASIMED (JFM), 2026)
Background: Fungal infections (mycoses) are common health problems in Indonesia, where tropical climatic conditions favor fungal growth. These infections are generally classified into dermatophytosis and non-dermatophytosis and are commonly treated using synthetic antifungal agents such as ketoconazole, which may cause adverse effects. Therefore, safer natural alternatives are needed. Pineapple rind and foliage crown (Ananas comosus L. Merr), which are typically discarded as agricultural waste, contain bioactive compounds with potential antifungal activity, including flavonoids, alkaloids, saponins, and tannins. Purpose: This study aimed to evaluate the antifungal activity of ethanol extracts from pineapple rind and foliage crown waste against Trichophyton rubrum and Aspergillus niger. Methods: An experimental study was conducted using the Kirby–Bauer disc diffusion method with extract concentrations of 25%, 50%, and 75%, along with negative (0%) and positive (ketoconazole) controls. Results: Both pineapple rind and foliage crown extracts inhibited the growth of T. rubrum and A. niger. The 75% concentration exhibited the largest inhibition zones, indicating the highest antifungal effectiveness. Conclusion: These findings suggest that pineapple rind and foliage crown waste have potential as natural antifungal agents.